Professores do curso de licenciatura em Matemática em início de carreira no ensino superior - Silva, Sandra Regina Lima dos Santos (2014)
The aim of this research was to identify and question the challenges and difficulties faced by training teachers in the beginning of their career in Higher Education as well their ways of response to those demands. The study was carried with teachers who have actuated in Mathmatics undergraduate programs ministered by institutions located in the states of São Paulo, Paraná and Rio Grande do Sul. Out of a total of fourteen respondents, five have worked in public colleges and nine in private ones. This survey applied the qualitative approach as a methodologic procedure by using semistructured interviews and questionnaire. The research permitted to observe the Mathematics training teacher profile and his corresponding instruction, as well the types of teaching access and professional recognition. In order to find such data, we analysed the specificity and difficulties of teacher's conduction and the strategies which best respond to practice requirements considering the institutional conditions and working implications for the beginners of this segment. The cornerstone of this study lies on Higher Education teaching, training educators in the beginning of their career and their instruction learning. In general, the analysis of the data make it possible for us to state that beginner teachers face pedagogic and institutional challenges. In order to cope with that, such educator comes across situations which require a complex formative awareness about his teaching-learning process in Higher Education. The survey brought strong evidences that the support given by expert colleagues improves the specificity of beginners' practice. Through the analysis of this Mathematics beginner professoriate some particular elements were unveiled. They have been worthy when students respect them. In turn, their prior experience in Basic Education has seen as a condition to structure their practice in teaching programs. Moreover, they work in a pleasant and solidary environment which provides exchanges of pedagogic material and guiding with their partners. Finally, the results demonstrated that the beginning of teaching career has been founded apart when it comes to the dilemmas shown in this stage. In this case, training educadors have been seeking alternatives to cope with those problems evidencing that they are capable of building up their own learning from the pedagogic practice